Impaired Fasting Glucose Is Associated With Renal Hyperfiltration in the General Population - Melsom, Toralf; Mathisen, Ulla Dorte; Ingebretsen, Ole C; Jenssen, Trond Geir; Njølstad, Inger; Solbu, Marit Dahl; Toft, Ingrid; Eriksen, Bjørn Odvar (Diabetes Care, 2011)
Increased glomerular filtration rate (GFR), also called hyperfiltration, is a proposed mechanism for renal injury in diabetes. The causes of hyperfiltration in individuals without diabetes are largely unknown, including the possible role of borderline hyperglycemia. We assessed whether impaired fasting glucose (IFG; 5.6–6.9 mmol/L), elevated HbA1c, or hyperinsulinemia are associated with hyperfiltration in the general middle-aged population. A total of 1,560 individuals, aged 50–62 years without diabetes, were included in the Renal Iohexol Clearance Survey in Tromsø 6 (RENIS-T6). GFR was measured as single-sample plasma iohexol clearance. Hyperfiltration was defined as GFR >90th percentile, adjusted for sex, age, weight, height, and use of renin-angiotensin system inhibitors. Participants with IFG had a multivariable-adjusted odds ratio of 1.56 (95% CI 1.07–2.25) for hyperfiltration compared with individuals with normal fasting glucose. Odds ratios (95% CI) of hyperfiltration calculated for a 1-unit increase in fasting plasma glucose (FPG) and HbA1c, after multivariable-adjustment, were 1.97 (1.36–2.85) and 2.23 (1.30–3.86). There was no association between fasting insulin levels and hyperfiltration. A nonlinear association between FPG and GFR was observed (df = 3, P < 0.0001). GFR increased with higher glucose levels, with a steeper slope beginning at FPG ≥5.4 mmol/L. Borderline hyperglycemia was associated with hyperfiltration, whereas hyperinsulinemia was not. Longitudinal studies are needed to investigate whether the hyperfiltration associated with IFG is a risk factor for renal injury in the general population.